Holding down half the sky: female knowledge workers and flexible employment in China's publishing conglomerates. (1st December 2015) - ,; ,
Abstract : Drawing on surveys and in-depth interviews with educated women working in the contemporary Chinese publishing industry, this article details the deterioration in their living and working conditions produced by the combination of conglomeration within the industry and the erosion of the state-supported welfare system. It pays particular attention to the role of flexible employment practices and revised organisational hierarchies in reshaping their work to fit the contemporary market for cultural production. These innovations, it is argued, have created more precarious working conditions, devalued their labour and left them less protected and more exploited.